2009
DOI: 10.1007/s10705-009-9330-3
|View full text |Cite
|
Sign up to set email alerts
|

How much do water deficits alter the nitrogen nutrition status of forage crops?

Abstract: Water deficits alter the nitrogen nutrition of crops. In grasslands, this has a major impact on both forage yield and nitrogen fluxes in the soil. It is important to assess the N balance in order to adjust fertilization to the expected needs of the crop and thus minimize any environmentally negative impacts of crops. Grassland species, including grasses, display a diverse ability to utilise soil resources. Nitrogen fluxes and the nitrogen absorption by grass swards of two species with contrasting rooting depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 37 publications
4
26
0
Order By: Relevance
“…5) suggests incomplete N uptake from the soil due to relatively high N availability from fertiliser, soil N mineralisation, and/or symbiotic N 2 fixation. Under the drought treatment, however, the consistently low levels of plant-available soil N in all species-fertiliser treatments suggest severe inhibition of soil N mineralisation and/or of mineral N fluxes due to very low levels of soil water (Borken and Matzner 2009;Burke et al 1997;Durand et al 2010). Restrictions in the availability of mineral soil N must have been pervasive under drought as they could not be offset by additional N fertilisation of 60 kg ha −1 to L. perenne (Lp vs. Lp highN ), a clear contrast to rainfed control conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5) suggests incomplete N uptake from the soil due to relatively high N availability from fertiliser, soil N mineralisation, and/or symbiotic N 2 fixation. Under the drought treatment, however, the consistently low levels of plant-available soil N in all species-fertiliser treatments suggest severe inhibition of soil N mineralisation and/or of mineral N fluxes due to very low levels of soil water (Borken and Matzner 2009;Burke et al 1997;Durand et al 2010). Restrictions in the availability of mineral soil N must have been pervasive under drought as they could not be offset by additional N fertilisation of 60 kg ha −1 to L. perenne (Lp vs. Lp highN ), a clear contrast to rainfed control conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from water, nitrogen (N) can become drought-limited (Colman and Lazenby 1975). Plantavailable soil N is affected by drought through restricted water fluxes, reduced N mineralisation, and restricted transport of mineral N (Borken and Matzner 2009;Durand et al 2010). Depending on the degree of drought severity, both water and N can simultaneously affect biomass production (Hooper and Johnson 1999); despite this being known, few studies have addressed drought-induced impacts on plant growth of other factors than water (but see Bollig and Feller 2014;Gonzalez-Dugo et al 2005;Hofer et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…50 Finally, drought also modifies the availability of nutrients in the soil. 52 For instance, nitrogen (N) uptake is smaller in some species growing in dry soils, 53 which may then accumulate in the soil, with possible effects on the grassland seed bank 54 and soil pH, 55 which in turn may have consequences for the persistence of seeds in grasslands soils. 56 Previous studies at our experimental site showed that, comparing control and drought treatments, the mean plant N supply (the sum of plant-available nitrate and ammonium) was doubled after drought.…”
Section: Discussionmentioning
confidence: 99%
“…Labelled N of whole plants was lower when the plants were completely defoliated (100 % final defoliation treatment), probably due to a negative effect of defoliation on root dry mass and specific uptake of N. Additionally, since all leaf area was removed, low soil N flux induced by lower plant transpiration may also have contributed to a reduction of N uptake of plants from the 100 % defoliation treatment (Durand et al, 2010). Lestienne et al (2006) observed a reduction in N uptake of Lolium perenne with the removal of more than 75 % leaf area when N supply was high and suggested this was related to a negative effect of defoliation intensity on root dry mass.…”
Section: Nitrogen Uptakementioning
confidence: 99%
“…Nitrogen availability for regrowth may be reduced after defoliation due to a decrease in the N pool from senescing leaves, lower root growth or a reduction in soil N flux induced by lower crop transpiration (Lestienne et al, 2006;Gastal et al, 2010;Durand et al, 2010). On the other hand, plants can adapt to defoliation intensity by changing their shoot and root morphology and growth rate (Matthew et al, 2000;Gastal et al, 2010) and, consequently, changing both the amount of shoot material and N stores bellow cutting height and the exploitation of the soil by roots for water and nutrients uptake.…”
Section: Introductionmentioning
confidence: 99%